Regional Differentials in Early Antenatal Care, Health Facility Delivery and Early Postnatal Care among Women in Uganda - Atuhaire, Ruth; Wamala, Robert; Atuhaire, Leonard K.; Nansubuga, Elizabeth (Journal of Economics and Behavioral Studies, 2021)
This study aimed at examining regional differentials in maternal healthcare services in Uganda. Using a sample of 1,521 women of reproductive ages (15-49) from Eastern and Western sub-regions of Uganda, and non-linear Oaxaca’ Blinder Multivariate Decomposition method, we assessed differentials in utilization of early antenatal care, health facility delivery and early postnatal care services among the women, henceforth, establishing main predictors of regional inequalities that will enable policymakers to make better evenly interventions and focused decisions. The study reveals that differentials in the utilization of maternal healthcare services are not only hindered by social and economic barriers, but also widespread disparities in the utilization of existing services. Significant differentials were attributed to both variation in women’s characteristics and effects of coefficients. Findings showed that the gap in early antenatal care would reduce on average by 31.6% and 34.7% of differences in availability of community health workers and media exposure respectively, were to disappear. Furthermore, the gap would increase on average by 68.8% and 12.6% in absence of the variation in effects of maternal education, and wealth respectively. The gap in health facility delivery would reduce on average by 24.6% and 37.2% of differences in community health worker availability and media exposure were to disappear respectively and increase on average by 54.9% in the absence of variations in effects of maternal education. The gap in EPNC would reduce on average by 18.5% and 17.17% of differences in maternal education and community health worker availability were to disappear respectively and increase on average by 52.8% and 8.4% in the absence of the variation in effects of maternal education and wealth respectively. Progress towards equitable maternal health care should focus more on strategies that guarantee even distribution of community health workers, broad dissemination of maternal healthcare information and girl child education completion in Uganda.
Keywords: Regional decomposition; Oaxaca’ Blinder; Early ANC; Health facility delivery; EPNC